Late Quaternary tectonics controlled by fault reactivation. Insights from a local transpressional system in the intermontane Lerma valley, Cordillera Oriental, NW Argentina. (November 2019) - García, Víctor H.; Hongn, Fernando; Yagupsky, Daniel; Pingel, Heiko; Kinnaird, Timothy; Winocur, Diego; Cristallini, Ernesto; Robinson, Ruth A.J.; Strecker, Manfred R.
Abstract: We analyzed the Lomas de Carabajal area in the intermontane Lerma valley of the Cordillera Oriental to assess the level of neotectonic activity in a densely populated region of northwestern Argentina. In this region, Plio-Pleistocene synorogenic conglomerates are deformed, locally associated with high-angle faults, and NNW-SSE oriented en-échelon folds characterized by wavelengths of <1 km. The deformed Quaternary units follow the same pattern of deformation as observed in the underlying Neogene deposits; growth-strata geometries are observed near faults. This configuration is compatible with local left-lateral transpressional tectonism driven by ENE-WSW buttressing against the NW-oriented border of a Cretaceous extensional basin (Alemanía sub-basin). Optically Stimulated Luminescence analysis of sandy-silty layers interbedded within the folded late Pleistocene conglomeratic sequence helps to determine uplift rates of 0.83–0.87 mm/a during the last 30–40 ka. Nearby the Lomas de Carabajal, a WNW-striking, 3-m-high fault scarp disrupts radiocarbon dated, 10-ka-old loessic deposits providing a Holocene mean uplift rate of 0.30 mm/a. Our data unambiguously show that shallow crustal deformation in the intermontane Lerma valley is ongoing; some of this deformation may be associated with seismicity. Our findings support the notion of temporally and spatially disparate deformation processes in the broken foreland of the northwestern Argentinean Andes. Highlights: New key structural and morphological data were collected in the Lomas de Carabajal of NW Argentina. Deformed late Pleistocene to Holocene deposits and nearby seismicity are evidence of active tectonics in the region. Left-lateral transpressive system evidenced by en-échelon fold axes arrangement. Late Pleistocene to Holocene uplift and displacement rates were established for the seismogenic structures by means of OSL and 14 C dating of deformed sediments. Maximum potential earthquake magnitudes are Mw 6.4 based on empirical scaling relationships.